Identifying tumor antigens and immune subtypes of gastrointestinal MALT lymphoma for immunotherapy development - Jiang, Xinlu; Zhang, Huanhuan; Ni, Jinju; Zhang, Xu; Ding, Kaiyang (Frontiers in Oncology, 2022)
MALT lymphoma is an extranodal B-cell lymphoma of the marginal zone of mucosa-associated lymphoid tissue (MALT), caused by malignant transformation of B-cells in the marginal zone. In this work, we aim to explore the potential relationship between MALT lymphoma and DLBCL. Vaccines derived from messenger ribonucleic acid (mRNA) may provide satisfactory results. Despite being a promising treatment option, immunotherapy isn't widely used in treating renal cell carcinoma, as only a few patients respond to the treatment. The Cancer Genome Atlas (TCGA) analysis revealed gene expression profiles and clinical information. Antigen-presenting cells infiltrated the immune system using TIMER tool (http://timer.cistrome.org/). GDSC (Genomics of Drug Sensitivity in Cancer) data were used to estimate drug sensitivity. Immune-related genes were associated with a better prognosis in MALT lymphoma patients and higher levels of antigen-presenting cells. There is a significant relationship between these immune subtypes and immunological checkpoints, immunogenic cell death regulators, and prognostic variables for MALT lymphoma patients. In this study, we provide a theoretical foundation for the development of mRNA vaccines and suggest that KLHL14 could potentially be used as antigens to develop mRNA vaccines for MALT lymphoma.